Student Satisfaction Index on Lecturer Performance Based on E-learning and Competence - Ana Afida; Achmad Junaidi (At-Taqaddum, 2021)
Student satisfaction in the learning process is influenced by various factors, one of which is related to the performance and competence of lecturers. This study aims to identify student satisfaction with the lecture process based on lecturer performance competencies. The research method used is a survey research method. The sampling technique in this study used a non-probability incidental sampling technique. This study was conducted to measure the quality of lecturer performance from students' perspectives. The unit of research analysis is the individual (student). Respondents were sent randomly using the Google Drive system in connection with the COVID-19 pandemic, which impacted the online lecture system. The results of the analysis show that the performance of lecturers with an IKM score of 2.82 (70.5), where the service quality is category B. The quality of service B shows that the performance of UIN Walisongo lecturers is categorized as good. Of the 14 elements studied, there is one unsatisfactory indicator: Timeliness of attendance Lecturers have an average performance score of 2.46. The other 13 indicators assessed by Walisongo State Islamic University students had good categories.